THE INFLUENCE OF PRINCIPAL LEADERSHIP, WORK MOTIVATION, ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) ON THE PERFORMANCE OF MUHAMMADIYAH HIGH SCHOOL / VOCATIONAL HIGH SCHOOL TEACHERS IN WONOSOBO REGENCY - Laily Mardiyati; Imron Imron; Imam Mawardi (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
This study aims to determine the effect of principal's leadership, work motivation and OCB on the performance of Muhammadiyah high school/vocational teachers throughout Wonosobo Regency. This research is included in field research or field research, with quantitative research methods. This thesis research took place at SMA/SMK Muhammadiyah in Wonosobo Regency. The population in this study were teachers who worked in SMA/SMK Muhammadiyah in Wonosobo Regency, totaling 134 and the sample used was 60 respondents/teachers. The data collection method used is a questionnaire method, while the analytical technique used consists of classical assumption test and regression analysis which is processed with the help of the SPSS for windows 26.00 program. This is evidenced by the t value for the effect of 3.408 which is greater than the t table value for df 58 at t 0.025, which is 2.00 with a significance level of 0.001. The effect of work motivation partially on teacher performance has also been shown to be influential and significant, as evidenced by the t count value of 2.633 (> t table = 2.00) with a significance level of 0.011. While the partial effect of OCB on teacher performance has also been shown to be influential and significant, as evidenced by the t count value of 3.596 (> t table = 2.00) with a significance level of 0.001. Together, the three variables have been shown to have an effect on teacher performance. This can be proven through the results of the F test which results in the calculated F value of 199.663 which is greater than the F table value of 2.00 with a significance level of 0.000. Based on the results of the study, in order to improve teacher performance, improvements to the principal's leadership, work motivation and OCB of teachers need to be improved first.